A caregiver-reported global severity assessment in pediatric atopic eczema: the Comano score - Mattia Giovannini; Davide Geat; Gabriele Barlocco; Riccardo Pertile; Francesca Mori; Cesare Filippeschi; Elio Novembre; Mario Cristofolini; Ermanno Baldo (BMC, 2020)
Abstract Atopic eczema (AE) is the most common inflammatory skin disease in infancy and its prevalence is rising worldwide. It has a wide social impact on the affected children and their families' lives. AE can have a chronic and heterogeneous course, with periods of remission and relapse of the clinical manifestations. For this reason, its severity assessment through standardized outcome measures becomes a fundamental guide for health professionals, who can manage AE following evidence-based medicine principles in their everyday clinical practice or in clinical trials. Several scoring systems have been recognized to assess the clinical manifestations of AE, both from the physician's and the patient's point of view. Despite the scoring systems standardized for adults, there are very few published options about the expression of a patient/caregiver-centered global severity assessment specifically for pediatric AE. For this reason, the aim of our study was to evaluate a new, quick, user-friendly and feasible caregiver-reported global severity assessment for pediatric AE. Based on a 0-10 numerical rating scale in pediatric AE, we named this scoring system the Comano score. We carried out a cross-sectional observational study enrolling a total of 867 patients aged from 1 to 16 years (males 49.5%, mean patient's age 5.9 years, standard deviation ±3.6 years) with a previous doctor-confirmed diagnosis of AE, who underwent balneotherapy at Comano Thermal Center (Comano, Trentino, Italy). A strong correlation between Comano score and SCORing Atopic Dermatitis (SCORAD) was observed (r = 0.74, p < 0.0001). According to our results, the Comano score may be a promising new tool for the expression of a caregiver-reported global severity assessment in pediatric AE. However, further data are needed to confirm our preliminary findings before health professionals can use this scoring system in their everyday clinical practice to manage pediatric AE. Still, as a patient-focused measure, the Comano score may facilitate delivering person-centered care so as to define a measure for a clinical impact that can be meaningful to the subject, which is gaining importance in modern medicine.